Analgesia after Lower Abdominal Surgery in Children Treated with Caudal Bupivacaine Versus a Bupivacaine-Tramadol Combination - Ghulam Murtaza Shaikh, Muhammad Muazzam Butt, Mohsin Riaz Askri, Eram Shahzadi, Shumyala Maqbool, Syed Imtiaz Ali Zaidi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Postoperative pain management in pediatric patients is essential in controlling pain and in improving recovery results. The technique of caudal epidural analgesia is widely used in pediatric lower abdominal surgeries and adding tramadol to bupivacine has been effective in producing increased analgesic effect. Objective: To evaluate the efficacy of tramadol as an adjuvant to bupivacaine for caudal analgesia in pediatric patients undergoing lower abdominal surgeries. Material and Methods: This randomized controlled trial was performed at the Fatima Hospital Baqai Medical University Karachi, from January 2023 to June 2023. Total 64 pediatric patients aged 2–12 years undergoing elective lower abdominal surgeries were randomly assigned into two groups of 32 patients each. In Group A, caudal bupivacaine (0.25 %, 1 mL/kg,) was administered while in Group B bupivacaine (0.25 %, 1 mL/kg) and tramadol (1 mg/kg.) in combination with each other. Evaluation of postoperative pain was performed using the FLACC scale at 1, 2, 4, 6, and 12, and 24 hours in the postoperative period. The primary result was the duration of analgesia, secondary results included the pain scores, requirements for rescue analgesia and adverse effects. The statistical analysis was done using SPSS version 24. Results: Mean pain scores were significantly lower for the bupivacaine-tramadol group at all time points (p < 0.001) and the duration of analgesia in this group was longer (11.99 ± 2.00 hours versus 5.68 ± 0.95 hours, p < 0.001). The bupivacaine-tramadol group also had lower rescue analgesia requirements (0.56 ± 0.50 doses vs 2.78 ± 0.83 doses; p < 0.001). There was no significant increase in adverse effects. Conclusion: For pediatric patients requiring caudal analgesia, the addition of tramadol to bupivacaine provides prolonged analgesia with a favorable safety profile, and results in improved postoperative pain management. Keywords: Bupivacaine, Tramadol, Caudal analgesia, Pediatric surgery, Postoperative pain.